Time series of scallop gaping activity (valvometry data) recorded in situ (bay of Saint Brieuc) in autumn 2021 - Elie Retailleau (PANGAEA, 2022)
Data were acquired to study the natural daily gaping activity of the large scallop (Pecten maximus). Autonomous valvometers (Valve-Trek; Technosmart Europe srl, www.technosmart.eu) were used to measure the valve opening (maximum distance betwee two valves) activity of the great scallops. Including Hall effect sensors, the valvometers were attached (glued with epoxy resin) to the left valve of the scallops to record magnetic field variations of magnets placed (glued with epoxy resin) on the right valve. The sampling frequency of the sensors was set to 2 Hz to record low-frequency movements of the bivalves (variation in their opening status). This sampling rate (0.5 s) also allowed for the recording of punctual behaviors produced by faster movements of their valves (e.g., jumps, partial closures). The sensors and magnets were positioned uniformly on all individuals with the valvometer fixed at the ventral edge on the antero-posterior axis of the scallops. The size of these sensors (length: 22 mm; width: 13 mm; height: 8 mm; weight: 3.5 g) was consistent with potential epibionts of scallops such as the slipper-limpet (Crepidula fornicata). In September 2021, 25 adult great scallops (size: 97.32 mm ± 5.09, antero-posterior axis) equipped with valvometers were deployed for a period of 19 days within the Bay of Saint Brieuc (Brittany, France), about 16.5 nautical miles from the coast (48.895N, -2.580W). These individuals were collected nine days earlier by scuba divers at the Porz ar Birnec site (48.744N, -2.941W; Bay of Saint Brieuc) and then kept in tanks (Plouezec, Brittany, France) to equip them and wait for the deployment mission. During this period of captivity (8 days), scallops were isolated in 0.16 m^2 compartments within closed-circuit tanks with a constant temperature of 16°C. They were not fed. Scallops were then deployed in situ from a boat, in individual hard-bottom PVC cages of 0.215 m^2 (length: 50 cm; width: 43 cm; height: 40 cm) separated by 10 m, allowing each individual to be considered independent during the field experiment (no interaction possible between the sensors and between individuals). Since the sides of the cages (except the bottom) consisted of wide mesh nets (35 mm side), it is unlikely that they affected the exposure of scallops to local current and natural light. With a soft substrate and depths of 35–40 m, the study site is part of one of the largest source areas of scallops in France. Once the scallops were retrieved after 19 days, all recorded time series were calibrated to convert magnetic field intensity variations emitted by magnets (mV) into accurate valve opening distances (mm). Following a standard procedure, this calibration step was performed after the deployment by computing individual calibration curves linking recorded valvometer values to a set of known inter-valve distance (0, 5, 10, 15, 20, 25, 30, 35 mm). This procedure was repeated for each individual separately. We first severed their adductor muscle. Then, the Hall voltages corresponding to the different calibration distances were measured, by inserting a series of calibrated wedges between their valves. The data were then converted to angle (degree) by considering the size of the scallops.